2015
DOI: 10.1103/physreva.91.053823
|View full text |Cite
|
Sign up to set email alerts
|

Phase-sensitive Kerr nonlinearity for closed-loop quantum systems

Abstract: The third-order susceptibility is investigated in a five-level atomic system in which the laser beams couple the ground state to a four-level closed-loop system. It is found that under the condition of the multiphoton resonance, one can enhance the Kerr nonlinearity of such a medium by properly adjusting the amplitudes and phases of the applied fields. In this case, the linear and nonlinear absorption reduce considerably in a region with a positive group velocity. It is demonstrated that the third-order suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…The self Kerr nonlinearity of the two, three and fourlevel atomic system has been studied theoretically and experimentally by Sheng et al [33]. Recently, Hamedi and Juzeliūnas proposed a phase sensitive model for achieving giant Kerr nonlinearity in a closed-loop configuration [34]. They realized that under the multiphoton resonance conditions, the Kerr nonlinearity can be manipulated by amplitudes and phases of the applied fields.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The self Kerr nonlinearity of the two, three and fourlevel atomic system has been studied theoretically and experimentally by Sheng et al [33]. Recently, Hamedi and Juzeliūnas proposed a phase sensitive model for achieving giant Kerr nonlinearity in a closed-loop configuration [34]. They realized that under the multiphoton resonance conditions, the Kerr nonlinearity can be manipulated by amplitudes and phases of the applied fields.…”
Section: Introductionmentioning
confidence: 98%
“…In nonlinear optics, due to significant role of Kerr nonlinearity in some important phenomena [26,27], it is favoraitable to have giant Kerr nonlinearity in low light intensities [28]. Recently it has been shown that the giant enhanced Kerr nonlinearity in multi-level atomic systems with zero linear absorption can be possible by different mechanisms [29][30][31][32][33][34][35][36][37][38]. Niu et al investigated giant Kerr nonlinearity via double dark resonances in a four-level atomic system [35].…”
Section: Introductionmentioning
confidence: 99%
“…where the detaied expressions for the coefficients κ 0 , κ 1 and κ 2 are given in Appendix C, while S 1 (ω) and Q(ω) can be found in Appendix D. In equation (30), κ i = d j κ(ω) dω j | ω=0 with j = 0, 1, 2 are the dispersion coefficients in different orders. In general, the real part of κ 0 = Υ + iχ/2 defines the phase shift Υ per unit length, while the imaginary part indicates the linear absorption χ of the probe pulse.…”
Section: Linear and Nonlinear Pulse Propagation In Combined Tripod Anmentioning
confidence: 99%
“…Closed-loop quantum configurations [30,45,[52][53][54][55] represent a class of atom-light coupling schemes in which the driving fields acting on atoms build closed paths for the transitions between atomic levels. The interference between different paths makes the system sensitive to relative phases of the applied fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation